Arabidopsis LEAFY COTYLEDON1 controls cell fate determination during post-embryonic development - Huang, Mingkun; Hu, Yilong; Liu, Xu; Li, Yuge; Hou, Xingliang (Frontiers in Plant Science, 2015)
Arabidopsis LEAFY COTYLEDON1 (LEC1) transcription factor is a master regulator that shapes plant embryo development and post-embryonic seedling establishment. Loss-of-function of LEC1 alters the cotyledon identity, causing the formation of ectopic trichomes, which does not occur in wild-type seedlings, implying that LEC1 might regulate embryonic cell fate determination during post-embryonic development. To test this hypothesis, we compared the expression of trichome development-related genes between the wild-type and the lec1 mutant. We observed that transcripts of GL1, GL2 and GL3, genes encoding the positive regulators in trichome development, were significantly upregulated, while the TCL2, ETC1 and ETC2 genes, encoding the negative regulators in trichome development, were downregulated in the lec1 mutant. Furthermore, overexpression of LEC1 activated the expressions of TCL2, CPC and ETC1, resulting in production of cotyledonary leaves with no or fewer trichomes during vegetative development. In addition, we demonstrated that LEC1 interacts with TCL2 in yeast and in vitro. A genetic experiment showed that loss-of-function of GL2 rescued the ectopic trichome formation in the lec1 mutant. These findings strongly support that LEC1 regulates trichome development, providing direct evidence for the role of LEC1 in cell fate determination during post-embryonic development.